Mycorrhizal Symbiotic Efficiency on C3 and C4 Plants under Salinity Stress – A Meta-Analysis - Chandrasekaran, Murugesan; Kim, Kiyoon; Krishnamoorthy, Ramasamy; Walitang, Denver; Sundaram, Subbiah; Joe, Manoharan M.; Selvakumar, Gopal; Hu, Shuijin; Oh, Sang-Hyon; Sa, Tongmin (Frontiers in Microbiology, 2016)
A wide range of C3 and C4 plant species could acclimatize and grow under the impact of salinity stress. Symbiotic relationship between plant roots and arbuscular mycorrhizal fungi (AMF) are widespread and are well known to ameliorate the influence of salinity stress on agro-ecosystem. In the present study, we sought to understand the phenomenon of variability on AMF symbiotic relationship on saline stress amelioration in C3 and C4 plants. Thus, the objective was to compare varied mycorrhizal symbiotic relationship between C3 and C4 plants in saline conditions. To accomplish the above mentioned objective, we conducted a random effects models meta-analysis across 60 published studies. An effect size was calculated as the difference in mycorrhizal responses between the AMF inoculated plants and its corresponding control under saline conditions. Responses were compared between (i) identity of AMF species and AMF inoculation, (ii) identity of host plants (C3 vs. C4) and plant functional groups, (iii) soil texture and level of salinity and (iv) experimental condition (greenhouse vs. field). Results indicate that both C3 and C4 plants under saline condition responded positively to AMF inoculation, thereby overcoming the predicted effects of symbiotic efficiency. Although C3 and C4 plants showed positive effects under low (EC<4 ds/m) and high (>8 ds/m) saline conditions, C3 plants showed significant effects for mycorrhizal inoculation over C4 plants. Among the plant types, C4 annual and perennial plants, C4 herbs and C4 dicot had a significant effect over other counterparts. Between single and mixed AMF inoculants, single inoculants Rhizophagus intraradices had a positive effect on C3 plants whereas Funneliformis mosseae had a positive effect on C4 plants than other species. In all of the observed studies, mycorrhizal inoculation showed positive effects on shoot, root and total biomass, and in nitrogen, phosphorous and potassium (K) uptake. However, it showed negative effects in sodium (Na) uptake in both C3 and C4 plants. This influence, owing to mycorrhizal inoculation, was significantly higher in K uptake in C4 plants. For our analysis, we concluded that AMF-inoculated C4 plants showed more competitive K+ ions uptake than C3 plants.